Penetration Testing on Metasploitable 2 (International Journal of Engineering and Computer Science, 2020)
Abstract— In this paper, we will discuss how to perform a penetration test on Metasploitable 2 using Metasploit. Metasploitable 2 is a vulnerable system that we decide to use, as using some other system to do the same it would be considered as hacking and could have awful results. The primary purpose of this research is to tell about the various tools used when someone trying to find possible vulnerabilities in a system. By using the Metasploit system to test a system, we can find possible vulnerabilities that need to be fixed to protect and make the system better. Different areas like firewalls, network protocols, and other basic security is-sues will be explored in this research.While there are many other different ways to do penetration testing, but we decide to use Metasploit be-cause of its broad uses and simplicity. We will have the option of either using the command line within Metasploit or by using the community version of the product, which is mostly automated. Both alternatives will be explored in this paper. If anyone going through all of the steps given in this paper should be able to try and exploit any vulnerable system.